Drivers of social media marketing continuance among MSMEs in emerging economies - Putit, Lennora; Hamzah, Muhammad Iskandar; Abdullah, Mohamad Fariz; Syed Annuar, Sharifah Nurafizah; Yulianto, Arief (Faculty of Business and Management ; UiTM Press, 2025)
Entrepreneurial activities in many business sectors nowadays are immensely significant for economic growth and national development. The utilization of marketing tools via online digital platforms such as social media marketing, pay-per-click advertisements, and search engine optimization is also rapidly growing for many business activities. This study aims to examine micro, small and medium sized (MSMEs) entrepreneurs’ continued usage intention of social media marketing (SMM) within the gastronomic business sector. Drawing from the Technology Acceptance Model, it attempts to investigate whether perceived usefulness, perceived ease of use, facilitating conditions, and cost may influence their SMM usage. By using a non-probability sampling technique, 122 usable online survey questionnaire feedback were collected from MSME entrepreneurs in Malaysia. Data was analysed via SPSS version 26.0 to undertake both descriptive and multivariate analyses. Results demonstrate significant findings on all hypotheses. Perceived usefulness, perceived ease of use, cost, and facilitating conditions significantly influence MSMEs’ usage of SMM in enhancing their business performance. Several managerial contributions are further discussed.